2019
DOI: 10.3390/cancers11020216
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Long Non-Coding RNA MALAT1 in Cancer and Metastasis

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is one of the most abundant, long non-coding RNAs (lncRNAs) in normal tissues. This lncRNA is highly conserved among mammalian species, and based on in vitro results, has been reported to regulate alternative pre-mRNA splicing and gene expression. However, Malat1 knockout mice develop and grow normally, and do not show alterations in alternative splicing. While MALAT1 was originally described as a prognostic marker of lung cancer metastasis, emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
171
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 237 publications
(194 citation statements)
references
References 83 publications
2
171
1
2
Order By: Relevance
“…У 2003 році MALAT1 виявлено як транскрипт, асоційований із метастазуванням у пацієнтів із ранньою стадією недрібноклітинного раку легенів [3]. Сьогодні вважають, що основною функцією MALAT1 є регуляція експресії генів, пов'язаних із метастазами [4]. Крім того, доведена його важлива роль у таких клітинних процесах, як альтернативний сплайсинг, ядерна організація та епігенетична модуляція експресії генів [5].…”
unclassified
“…У 2003 році MALAT1 виявлено як транскрипт, асоційований із метастазуванням у пацієнтів із ранньою стадією недрібноклітинного раку легенів [3]. Сьогодні вважають, що основною функцією MALAT1 є регуляція експресії генів, пов'язаних із метастазами [4]. Крім того, доведена його важлива роль у таких клітинних процесах, як альтернативний сплайсинг, ядерна організація та епігенетична модуляція експресії генів [5].…”
unclassified
“…У 2003 році днРНК MALAT1 була виявлена як транскрипт, асоційований із метастазуванням у пацієнтів з ранньою стадією недрібноклітинного раку легенів [3]. Сьогодні вважається, що основна функція MALAT1 полягає у регуляції експресії генів, продукти яких причетні до утворення метастазів [7]. У роботі колективу Zhang et al було показано, що експресія MALAT1 корелює із розмірами пухлин у хворих на рак легенів, стадією та метастазами у регіонарні лімфовузли [8].…”
Section: погляд на проблемуunclassified
“…Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a well-known lncRNA associated with cancer angiogenesis and metastasis [189] . In EOC patients, Qiu et al [157] found elevated serum levels of exosomal MALAT1 that highly correlated with an advanced and metastatic phenotype of EOC and were an independent predictive factor for EOC overall survival.…”
Section: Circulating Lncrnas In Metastasismentioning
confidence: 99%